Characteristics of Wind Velocity and Temperature Change Near an Escarpment-Shaped Road Embankment - Young-Moon Kim; Ki-Pyo You; Jang-Youl You (The Scientific World Journal)
Artificial structures such as embankments built during the construction of highways influence the surrounding airflow. Various types of damage can occur due to changes in the wind velocity and temperature around highway embankments. However, no study has accurately measured micrometeorological changes (wind velocity and temperature) due to embankments. This study conducted a wind tunnel test and field measurement to identify changes in wind velocity and temperature before and after the construction of embankments around roads. Changes in wind velocity around an embankment after its construction were found to be influenced by the surrounding wind velocity, wind angle, and the level difference and distance from the embankment. When the level difference from the embankment was large and the distance was up to 3H, the degree of wind velocity declines was found to be large. In changes in reference wind velocities around the embankment, wind velocity increases were not proportional to the rate at which wind velocities declined. The construction of the embankment influenced surrounding temperatures. The degree of temperature change was large in locations with large level differences from the embankment at daybreak and during evening hours when wind velocity changes were small.